Intensive 7-day internet-delivered cognitive behaviour therapy for social anxiety disorder: study protocol for a randomised controlled trial - Kayla R. Steele; Emily Upton; Monique Holden; Amy Regan; Matthew J. Coleshill; Sophie Li; Amy E. Joubert; Alison E. J. Mahoney; Michael Millard; Jill M. Newby (Trials)
Abstract Background Social anxiety disorder (SAD) is a serious mental health disorder that when left untreated can lead to significant social, occupational, educational, and functional impairment. Cognitive behaviour therapy (CBT) is the recommended first-line psychological treatment for SAD and has been shown to be efficacious in face-to-face and online formats. However, treatment is lengthy, and many people drop out prematurely. Pilot research suggests that brief intensive internet CBT (iCBT) for SAD is feasible and acceptable, but further evaluation using randomised controlled trials (RCT) is needed. Methods A RCT to evaluate the acceptability, feasibility, and efficacy of an intensive 7-day iCBT program for adults diagnosed with SAD (with or without comorbid major depressive disorder) in comparison to a waitlist control (WLC) is currently in progress. Eligible participants will be randomised to an intervention or WLC group. Participants allocated to the intervention will complete 6 iCBT modules over 7 days, with CBT skills practice each day, and clinician guidance provided remotely by telephone and email. Participants allocated to the WLC will be given access to the program after a 6-week waiting period. All participants will complete assessments at baseline, 2 weeks and 6 weeks post-baseline. Outcome measures will assess for social anxiety (SIAS, SPS), depression (PHQ-9), personality (LPFS, PID-5-BF), and functioning (WSAS). Intention-to-treat linear mixed model analyses will be used to evaluate primary and secondary outcomes. Discussion Previous findings from a pilot trial showed that 7-day iCBT is feasible and acceptable to clients with SAD. Based on these findings, we expect the treatment group will improve significantly on measures of symptoms of social anxiety, depression, and functional impairment compared to the WLC, and these improvements will be sustained at 1-month follow-up. If demonstrated to be effective in this RCT, intensive 7-day iCBT for SAD is a novel way to deliver CBT more quickly, with potential to reach more clients and reduce drop-out rates. It has great potential to provide rapid symptom improvement to individuals with SAD. Trial registration This trial was prospectively registered with the Australian New Zealand Clinical Trials Registry on March 1, 2022 (ACTRN12622000361707).